Vuorovaikutuksen merkitys paikkaan sitoutumisessa : identiteetit ja sosiaalinen pääoma - Veripää, Heli (2018)
This research focuses on communication between employees and residents of the municipality. Especially the theory of communication and social capital relating to identitites are being studied. The doctoral thesis analyzes how municipal residents react to municipal reform.